Alterations of structural connectivity in episodic cluster headache: A graph theoretical analysis. (April 2019) - Ha, Sam Yeol; Park, Kang Min
Highlights: We evaluate structural volumes and connectivity in patients with cluster headache. The volumes of the left caudal anterior cingulate and postcentral gyrus are decreased. Significant hub re-organizations are found in the measures of local structural connectivity. These alterations are implicated in the pathogenesis of cluster headache. Abstract: We evaluated structural volumes and connectivity using graph theoretical analysis in patients with cluster headache. Ten patients with episodic cluster headache were recruited, who had a normal brain MRI on visual inspection. We also enrolled a control group of 20 healthy volunteers. All of the participants underwent 3-D volumetric T1-weighted imaging. We obtained the structural volumes using FreeSurfer image analysis and performed structural global and local connectivity analysis using BRAPH. The volumes of the left caudal anterior cingulate and postcentral gyrus were decreased in the patients with cluster headache compared to healthy individuals. In addition, in the measures of local structural connectivity, there was significant hub re-organization in the patients with cluster headache; the strength of the right frontopolar, left pericalcarine, and left posterior cingulate gyrus, the betweenness centrality of the right precentral and left pericalcarine gyrus, and the closeness centrality of the left pericalcarine and left posterior cingulate gyrus were decreased. Whereas the betweenness centrality of the right rostral middle frontal and left inferior temporal gyrus were increased in the patients with cluster headache. However, the measures of global structural connectivity were not different between the patients with cluster headache and healthy individuals. We demonstrate that the structural volumes and connectivity in patients with cluster headache are significantly different from those in healthy controls, especially revealing hub re-organization. These alterations are implicated in the pathogenesis of cluster headache and suggest that cluster headache is a network disease.